The Missio Dei as Flourishing Life - Niemandt, Nelus (Ecclesial Futures, 2020)
The idea of flourishing life has become one of the most important concepts in theological discourse, understanding human flourishing as at the heart of the Christian gospel. This literature and document-based research links the concept of flourishing life with the missio Dei and presents it as a contextually relevant theological interpretation of the missio Dei. The Church’s participation in God’s mission includes contributing towards flourishing life, and it concludes that such participation is of particular importance to ecclesiology. Missional ecclesiology is interested in everyday life and in faithful presence in everyday communities. The research follows an incarnational approach and argues for a Christian lifestyle focussed on the rhythms of everyday life in a way that appreciates the importance of the material life. It proposes attending to created life, sustained life and consummated life. The connection between flourishing life and the missio Dei underscores the important role of the Church in earthkeeping and affirms the Church’s calling to take responsibility for creation. The Church participates in sustaining life through four principles: conservancy, safeguarding, fruitfulness and Sabbath rest. In terms of consummation, the expectation of the end influences the here and now and how the church acts in everyday life.The research demonstrates that the connection between the missio Dei and flourishing life does have important implications for the Church’s public theology and the challenge to articulate a positive vision of life. It proposes a pluralistic social vision focussed on diversity, unconditional love, Jesus Christ as the light of the world, the moral equality of all human beings, and freedom of religion. The research concludes by attending to faithful presence as a way to translate the missio Dei into church praxis. Ecclesial life is located within the mutual concerns of the neighborhood. Faithful presence includes practices such as listening to the narrative of your place; enacting God’s peace in neigbourhoods; serving justice and reconciliation, allowing truth to flourish; and faithful reciprocal relationships with the created world.